2018
DOI: 10.1021/acs.molpharmaceut.8b00662
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Pump Substrates Shuttled to Cytosolic or Vesicular Compartments Exhibit Different Permeability in a Quantitative Human Blood–Brain Barrier Model

Abstract: Representative in vitro blood-brain barrier (BBB) models can support the development of strategies to efficiently deliver therapeutic drugs to the brain by aiding the characterization of their internalization, trafficking, and subsequent transport across the BBB. A collagen type I (COL1) hydrogel-based in vitro BBB model was developed to enable the simultaneous characterization of drug transport and intracellular processing using confocal microscopy, in a way that traditional insert-based in vitro BBB models c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
(90 reference statements)
2
10
0
Order By: Relevance
“…Accordingly, the decreasing serum concentration of exogenous IgG, which is exacerbated in FcRn knockout models or when the IgG lacks FcRn binding, and the presence of endogenous IgG represent experimental hurdles to the assessment of IgG transcytosis across BECs in vivo.Here we investigated the role of FcRn or other IgG-specific receptors in influencing the transcytosis of IgG across BECs in vitro using BEC-like cells derived from human induced pluripotent stem cells (iBECs). We have previously shown that iBECs exhibit permeability of IgG that is more restrictive than that observed for the rat BBB in vivo [24][25][26] , which supports its use as a representative BBB model. To compare the influence of FcRn engagement we assessed the intracellular processing and transcytosis of IgGs lacking human FcRn recognition, and we used human IgG as a control, at varying concentrations and in the presence of excess human IgG.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…Accordingly, the decreasing serum concentration of exogenous IgG, which is exacerbated in FcRn knockout models or when the IgG lacks FcRn binding, and the presence of endogenous IgG represent experimental hurdles to the assessment of IgG transcytosis across BECs in vivo.Here we investigated the role of FcRn or other IgG-specific receptors in influencing the transcytosis of IgG across BECs in vitro using BEC-like cells derived from human induced pluripotent stem cells (iBECs). We have previously shown that iBECs exhibit permeability of IgG that is more restrictive than that observed for the rat BBB in vivo [24][25][26] , which supports its use as a representative BBB model. To compare the influence of FcRn engagement we assessed the intracellular processing and transcytosis of IgGs lacking human FcRn recognition, and we used human IgG as a control, at varying concentrations and in the presence of excess human IgG.…”
mentioning
confidence: 56%
“…To assess the influence of FcRn-mediated processing, we used a comparative IgG-based approach, similar to a previous in vivo report 17 , which exploits the well-characterized stringency of human FcRn to only bind a unique sequence present on the Fc domain of some IgGs 19,20 . Visualization and quantification of transcytosis within the same timeframe was achieved by using our previously developed in vitro BBB model that consists of a monolayer of iBECs on a COL1-based hydrogel 25 . We observed that despite significant differences in lysosomal accumulation that was consistent with preferential FcRn-mediated recycling 19 , all tested IgGs exhibited comparable iBEC permeability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations